2022
DOI: 10.47115/bsagriculture.1071618
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Saturated and Unsaturated Fatty Acids in Second Crop Season Peanut Cultivation in the Eastern Mediterranean

Abstract: In this study; the saturated and unsaturated fatty acid composition of 11 different peanut cultivars, Runner (Georgia Green) Virginia (NC-7, Masal, Halisbey, Wilson, Com, Brantley, Duzici-1) Spanish (Florispan, Nigeria-1), widely grown in the eastern Mediterranean Transition Zone were determined. The research was carried out for two years (2020 to 2021) under second crop season conditions in the trial areas of the Oil Seeds Research Institute. The experiment was set up in a randomized block design with 3 repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These three peanut lines came to forefront with their O/L ratio and IV. It has been reported that O/L ratio of peanut genotypes depends on the genetic structure of genotype and environmental factors (Chowdhury et al, 2015;Mora-Escobedo et al, 2015;Gulluoglu et al, 2016;Yol et al, 2017;Ergun and Zarifikhosroshahi, 2020;Yilmaz, 2022). These findings were similar with the results of these researchers.…”
Section: Oil Quality Parameterssupporting
confidence: 87%
“…These three peanut lines came to forefront with their O/L ratio and IV. It has been reported that O/L ratio of peanut genotypes depends on the genetic structure of genotype and environmental factors (Chowdhury et al, 2015;Mora-Escobedo et al, 2015;Gulluoglu et al, 2016;Yol et al, 2017;Ergun and Zarifikhosroshahi, 2020;Yilmaz, 2022). These findings were similar with the results of these researchers.…”
Section: Oil Quality Parameterssupporting
confidence: 87%
“…The lowest iodine value (85.56) was recorded for control i.e., T9 while T5 treatment resulted in the highest iodine value (90.28) (Table 3). Yilmaz (2022) reported that iodine value varies between 85.99 and 88.28. Yururdurmaz (2022) stated that vermicompost applications improve the iodine value in cowpea and the ratio of vermicompost is important in iodine value.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the cultivar, peanut seeds contain 44-56% oil (Arıoğlu, 2014;Aşık et al, 2018). Peanut oil outperforms many vegetable oils in terms of flavor and survivability (Yaşlı et al, 2022;Yılmaz, 2022). After the oil is removed, the extract includes roughly 45% crude protein, 24% nitrogen-free basic substances, and 5.5% mineral substances (Arıoğlu, 2014).…”
Section: Introductionmentioning
confidence: 99%